2013
DOI: 10.1016/j.scitotenv.2012.12.088
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health of yellow perch Perca flavescens in selected tributaries of the Chesapeake Bay

Abstract: Iwanowicz, Luke R.; Minkkinen, Steven; Draugelis-Dale, Rassa O.; and Uphoff, James H., "Reproductive health of yellow perch Perca flavescens in selected tributaries of the Chesapeake Bay" (2013 H I G H L I G H T S► Reduced recruitment of yellow perch has occurred in urban tributaries of Chesapeake Bay. ► We compared reproductive health biomarkers in perch from two urban, one developing, two less developed watersheds. ► Lack of final maturation, abnormal yolk and zona pellucida were noted in females. ► Leydig … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 69 publications
0
12
1
Order By: Relevance
“…As part of a larger study to determine if chemical exposure is contributing to fish health issues being observed in the Chesapeake Bay watershed, [22][23][24] water samples were collected from three sites in this watershed (…”
Section: Streams In a Nationally Important Ecosystem: Chesapeake Baymentioning
confidence: 99%
“…As part of a larger study to determine if chemical exposure is contributing to fish health issues being observed in the Chesapeake Bay watershed, [22][23][24] water samples were collected from three sites in this watershed (…”
Section: Streams In a Nationally Important Ecosystem: Chesapeake Baymentioning
confidence: 99%
“…Lawrence and the upper Mississippi basins and on the Atlantic slope from Maine to Georgia [ 1 ]. It is a vital recreational and commercial species in Chesapeake Bay and the Great Lakes [ 2 ]. Yellow perch females outgrow males starting from 8–11 cm in total length and also have dominant and subordinated females [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…To assess the relative numbers of cells in early to late spermatogenic stages of maturation (Blazer et al, 2013;Kaufman and Nagler, 1987), a piece of testis was cut and weighed, then minced for 1 min in HBSS. The suspension was fixed in 4% paraformaldehyde (1:1 by volume) and stored at 4°C.…”
Section: Spermatogenic Stagingmentioning
confidence: 99%